2020
DOI: 10.1155/2020/4351671
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CAR10 Upregulates PDPK1 to Promote Cervical Cancer Development by Sponging miR-125b-5p

Abstract: Cervical cancer is one of the malignant tumors that seriously threaten women’s health. The mechanism of development needs to be deeply studied. In recent years, lncRNA has been identified as one of the important factors affecting the malignant progression of tumors. In this study, we illustrated the important mechanism of lncRNA CAR10 in the development of cervical cancer. We found that CAR10 is significantly increased in4 cervical cancer tissues and cells, which can promote the proliferation of cervical cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…25 A recent study has displayed that the expression of CAR10 in CC tissues and cells is dramatically increased, whereas up-regulation of CAR10 is closely correlated with lymph node metastasis. 11 In another study, OIP5-AS1 expression is markedly upregulated in CC cells, which is significantly associated with lymph node metastasis and tumor stage. 9 Similarly, we found that MIR4435-2HG expression was dramatically increased in CC tissues and cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…25 A recent study has displayed that the expression of CAR10 in CC tissues and cells is dramatically increased, whereas up-regulation of CAR10 is closely correlated with lymph node metastasis. 11 In another study, OIP5-AS1 expression is markedly upregulated in CC cells, which is significantly associated with lymph node metastasis and tumor stage. 9 Similarly, we found that MIR4435-2HG expression was dramatically increased in CC tissues and cells.…”
Section: Discussionmentioning
confidence: 93%
“…10 LncRNA CAR10 expression is significantly up-regulated in CC tissues, whereas overexpression of CAR10 can promote the proliferation of CC cells. 11 Additionally, the emerging evidences have displayed that lncRNA MIR4435-2HG is correlated with the occurrence and progression of many cancers. [12][13][14][15] A previous study has showed that overexpression of lncRNA MIR4435-2HG increases the cell viability and migration in colon adenocarcinoma (COAD) cells, which eventually promotes the development of colorectal cancer (CRC) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Serum miR-125b levels were found to be a useful diagnostic biomarker and a biomarker to predict the responses to chemotherapy in patients with epithelial ovarian cancer 27 . In cervical cancer, it was found that LncRNA CAR10 upregulated PDPK1 to promote cancer development by sponging miR-125b-5p 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we used a bioinformatics website to predict that miR-125b-5p is a shared miRNA of the LncRNA NEAT1 and YES1 genes. LncRNAs regulate gene expression mainly at the epigenetic level, transcription level and posttranscription level 28 . Transcription level and posttranscription level regulation are mainly mediated as molecular sponges, which inhibit the expression of target genes through binding and sponging miRNA 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al reported that CAR10 was upregulated in lung adenocarcinoma tissue, and it could promote lung adenocarcinoma metastasis through down-regulating miR-203 expression (9). Moreover, CAR10 has been con rmed promote cervical cancer development by sponging miR-125b-5p (10). However, till now, the role of CAR10 in PC remains unclear.…”
Section: Introductionmentioning
confidence: 99%